Synthesis, physico-chemical studies and biological evaluation of new metal complexes with some pyrazolone derivatives - Ahmed M. Ramadan; Asma A. Alshehri; Samir Bondock (Journal of Saudi Chemical Society)
A series of N-substituted-4-thiocarbamoyl-5-pyrazolone derivatives (HL1-HL4) is presented as chelating agents for complexation with Fe(III), Ni(II) and Cu(II) metal ions. The synthesized pyrazolone ligands and their newly metal complexes are characterized by different spectral and analytical methods such as UV–Vis, IR, 1H NMR, 13C NMR, ESR, MS, magnetic measurement, and TGA. The spectral data reveal that ligands coordinated to metal ions in a bidentate pattern via O & N atoms of the OH group at C(5) and thiocarbamoyl (–CSNHR) at C(4) of the pyrazolone ring. Also, the analytical data suggest the stoichiometries 2:3 (M:L) for both Cu(II) & Ni(II) complexes and 1:3 for Fe(III) complexes. Besides, the normal magnetic moments values for Fe(III) complexes confirm high spin octahedral structure while the diamagnetic nature of all Ni(II) complexes is consistent with square planar geometry. However, the subnormal magnetic values for Cu(II) complexes suggest the proposal of their binuclear structures. The ESR spectra of the Cu(II) complexes support the distorted square planar geometry with a considerably strong intradimeric spin-exchange interaction. Moreover, the anticancer, antibacterial and antifungal activities are screened. Among the synthesized compounds, HL4 ligand exhibits a significant broad spectrum of action against Gram-positive (S. aureus), Gram-negative bacteria (P. vulgaris), and antifungal potency against A. fumigatus & C. albicans in comparison with gentamicin and ketoconazole drug. Such potency of HL4 could be related to the insertion of the p-chloro in the phenyl group attached to the pharmacophoric thiocarbamoyl group at C(4). Furthermore, IC50 values of two Cu(II) complexes derived from HL2 and HL3 display nearly twofold or threefold more cytotoxicity impact against three cell lines (MCF-7, HCT116 and HepG-2) compared with cis-platin as positive control. Keywords: 5-Pyrazolones, Tautomerism, Thiocarbamoyl, Chelation modes, Antitumor evaluation, Antimicrobial activity